2007
DOI: 10.1097/iop.0b013e31814e0527
|View full text |Cite
|
Sign up to set email alerts
|

Subarachnoid Hemorrhage and Vasospastic Stroke After Self-Enucleation

Abstract: A 31-year-old intoxicated woman self-enucleated her left eye during an acute psychotic episode. CT revealed avulsion of the intracranial optic nerve, chiasmal edema, and adjacent subarachnoid hemorrhage. Exploration via transconjunctival orbitotomy was performed, and the globe and 4.8 cm of contiguous optic nerve were removed. The patient developed postoperative contralateral visual loss followed by middle cerebral artery vasospasm and bilateral cortical infarcts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…In 2007, Kotlus and Lo [22] published the first account of subarachnoid hemorrhage and eventual vasospastic stroke after autoenucleation. An acutely psychotic 31-year-old female patient self-enucleated her left eye.…”
Section: Neurovascular Complicationsmentioning
confidence: 99%
“…In 2007, Kotlus and Lo [22] published the first account of subarachnoid hemorrhage and eventual vasospastic stroke after autoenucleation. An acutely psychotic 31-year-old female patient self-enucleated her left eye.…”
Section: Neurovascular Complicationsmentioning
confidence: 99%
“…Rare cases of carotid laceration and subarachnoid hemorrhage have been reported following autoenucleation. 9,10 Intracranial hemorrhage following enucleation or exenteration appears to be an exceedingly rare event. Only one case of subarachnoid hemorrhage in the temporoparietal region following enucleation has been published and in this case, the authors concluded that the hemorrhage occurred secondary to an increase in blood pressure during extubation 11 ; of note, no angiography was performed to rule-out laceration.…”
Section: F Gonzalez and J R Bilykmentioning
confidence: 99%
“…Self-enucleation (oedipism) is an exceedingly rare form of self-mutilation generally associated with severe psychiatric disorders. [1][2][3][4] We describe a case in a patient with no psychiatric history that sustained a skull fracture in a motor vehicle crash. Toxicology studies revealed the presence of multiple substances including methamphetamines, cannabinoids, and benzodiazepines and the patient reported illicit use of the dissociative anesthetic phencyclidine.…”
Section: Polysubstance-induced Self-enucleation After Motor Vehicle Collisionmentioning
confidence: 99%
“…Autoenucleation is among the rarest forms of selfmutilation, and is usually associated with chronic and severe psychiatric disorder, namely schizophrenia. [1][2][3][4] It has been associated with a first psychiatric episode, which often occurs late in the second decade of life. No association of autoenucleation with acute skull fracture has been previously described.…”
Section: Polysubstance-induced Self-enucleation After Motor Vehicle Collisionmentioning
confidence: 99%
See 1 more Smart Citation